LITERATURE REVIEW: CORPORATE GOVERNANCE IN UNLISTED PUBLIC COMPANIES IN PUNE DISTRICT - Khatri, Anil; Lande, Ganesh Sambhaji (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This literature review explores the evolving landscape of corporate governance in unlisted companies, with a specific focus on the Pune District in India. While corporate governance has traditionally been emphasized in listed companies due to regulatory obligations, the growing importance of accountability, transparency, and sustainable management practices has extended its relevance to privately held and unlisted entities. The study critically examines conceptual frameworks, governance structures, ownership patterns, regulatory reforms, and emerging challenges faced by unlisted public companies in implementing effective governance mechanisms. Key issues such as board independence, succession planning, and the role of technology and ESG (Environmental, Social, and Governance) principles are discussed in the context of regional industrial dynamics. Empirical findings suggest that governance practices in unlisted public companies in Pune vary widely based on companies’ size, ownership structure, and access to external funding. The paper identifies critical research gaps and calls for further region-specific, empirical investigations to support policy development and promote stronger governance norms in the unlisted business sector